The design and revenue impact of a tax receipts lottery: A lab experiment in Tanzania - Cyril Chimilila; Remidius Ruhinduka; Vincent Leyaro (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2023)
Most sub-Saharan African countries are characterized by low tax compliance and low tax productivity. This study tests the effects of a tax lottery under alternative reward designs on compliance as an alternative policy option for addressing the problem of low tax receipts in Tanzania. The lab experiment involved the purchase of goods with a sample of 313 undergraduate students recruited from courses with and without tax specialization. The experiment participants were randomly assigned in control and treatment groups and thereafter assigned random endowment incomes. In the treatment groups two treatments were administered: a lottery of high probability and low rewards, and a lottery of low probability and high rewards, where eligibility for the lottery was restricted to those who paid VAT on the purchase (which would be cheaper otherwise). The results of the experiment show that a lottery of high reward has a higher impact on compliance and revenue. Our estimates show that the net revenue effects of these lotteries differ by 27 percent. Hence, the design of a tax lottery is important. Further, tax lotteries have the potential to improve taxpayer compliance and increasing revenue collection.
Keywords: H20; H26; H30; 330; VAT compliance; tax lottery experiment; rewards design; Tanzania